PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS KONTEKSTUAL PADA MATERISISTEM EKSKRESI UNTUK SMA - Yuliza, Mefa; Nurhadi, Nurhadi; Nerita, Siska (STKIP PGRI Sumbar, 2013)
ABSTRACTÂ In learning process the students donât master about the material that is abstract. To help the students to master it the students can use the worksheet. Should be made worksheet contextual. But worksheet that in the school is not contextual. Because of that is has developed worksheet based contextual on material excretion system in biology subject for high school. The purpose of this research is to know the validity and practicalities of worksheet based contextual. This research is a research that development by using 4-D models which consist of some steps, they are define, design, develop, and disseminate, but disseminate phase is not done. The test of validity is done by validator that consist of 2 lecturers and 3 of teachers SMAN 5 Solok Selatan. The test of practicalities is done by 3 of teachers and 30 of students of XII grades in SMAN 5 Solok Selatan. The data is analyzed by technic of presentation and the processy by descriptively. the result of validities test by validator showed that this worksheet on criteria valid is 80,18 %. The result of practicalities by the teachers showed that this worksheet in practical criteria is 78,59 % and the result of practicalities by the students show that this worksheet in practical criteria is 81,98 %. It can concluded worksheet based contextual on material of excretion system that has valid and practical.Â Â